PRESENT STATUS OF NESTING HABITAT OF GREEN TURTLE (Chelonia mydas) lN WEST JAVA-INDONESIA - Adriani Sri Nastiti Krismono; Amula Nurfiarini; Ahmad Fitrianto; Ngurah Nyoman Wiadnyana (Indonesian Fisheries Research Journal, 2009)
The coastal habitat condition much influences the moving of sea turtles to coast for nesting. In West Java Province there are some potential coasts as nesting habitat of sea turtles, but it has experiencing of many damage and has not been touched yet as the protected area for sea turtle nesting habitat.